2019
DOI: 10.2147/ndt.s220349
|View full text |Cite
|
Sign up to set email alerts
|

<p>Victimization In Childhood Affects Depression In Adulthood Via Neuroticism: A Path Analysis Study</p>

Abstract: Background: Adverse experiences, such as low care, overprotection, or abuse in childhood increase the likelihood of depression via their effects on personality traits. Similarly, being victimized in childhood may affect the likelihood of depression via personality traits. In this case-control study, we hypothesized that being victimized in childhood is associated with depression in adulthood via its effect on neuroticism, and verified this hypothesis using path analysis. Subjects and methods: Eighty-two major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…As mentioned in Introduction , the subjective nature of job stressors indicates that the intensity of stressors depends on individual personality traits, i.e., an individual’s sensitivity to stressors. Furthermore, neuroticism and resilience may be altered by childhood experiences, life events, and treatment ( 12 , 41 , 54 , 55 ). Therefore, resilience can be not only a moderator of stress but also a mediator of stress, as shown by the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in Introduction , the subjective nature of job stressors indicates that the intensity of stressors depends on individual personality traits, i.e., an individual’s sensitivity to stressors. Furthermore, neuroticism and resilience may be altered by childhood experiences, life events, and treatment ( 12 , 41 , 54 , 55 ). Therefore, resilience can be not only a moderator of stress but also a mediator of stress, as shown by the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The revised victimization scale of the National Institute for Educational Policy Research in Japan was used, as described in our previous study. 31 , 37 In our previous study, the score of the victimization scale significantly correlated with neuroticism, having depression, and the severity of depressive symptoms. 31 This scale is a self-report questionnaire that asks the frequency and degree of victimization of an individual in the community and school during childhood, using a 5-point Likert scale (0 to 4 points).…”
Section: Methodsmentioning
confidence: 83%
“…Tachi et al focused on mediating factors, and found that victimization experiences in childhood affect the onset of depression in adulthood and the severity of depression in depressed and healthy individuals through their effects on neuroticism. 31 In other words, the mediation of depressogenic effects by neuroticism is common in subjects who experienced victimization and maltreatment. 16 , 31 It is also known that parenting quality affects victimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since early adolescence is a critical period to the validity and reliability of the responses, results obtained regarding the psychological symptoms and bully involvement could considerably change according to who responded the information, future studies considering this will be needed. Compared to this study, pervious research on the impact of bullying/bullied involvement to later psychological symptoms was based on a longer observation period through adolescence (5,43) and adulthood (6,7,17,42). To investigate the long-term impact of bullying/bullied involvement, we plan to follow-up and obtain data at age 14 and later in TTC.…”
Section: Discussionmentioning
confidence: 99%